1996
DOI: 10.1111/j.2044-8260.1996.tb01167.x
|View full text |Cite
|
Sign up to set email alerts
|

A test of the hopelessness theory of depression in unemployed young adults

Abstract: Recent research has failed to support the prediction based on hopelessness theory that hopelessness mediates the full relationship between attributional style for negative outcomes and depression. A re-examination of hopelessness theory, however, provides the hypothesis that a measure of hopelessness containing items directly relevant to an ongoing negative life-event will mediate the full relationship between attributional style for negative outcomes and depression. Hopelessness theory was extended with a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
11
1
1
Order By: Relevance
“…Although speculative, a more suitable evaluation of the mediation hypothesis would be provided by a measure of event-specific hopelessness which is more susceptible to influence by the negative life-event precipitating the depression and by other vulnerability factors. Research by Lynd-Stevenson (1995, 1996 with the unemployed provides preliminary support for the present formulation because when the BHS was reworded to include items applicable to the unemployed, the event-specific measure of hopelessness was found to mediate the full relationship between attributional style and depression. Lynd-Stevenson ( 1995, 1996 failed, however, to examine the mediation hypothesis for stress-depression relationships and did not evaluate the moderation hypothesis.…”
Section: Robed M Lynd-stevensonmentioning
confidence: 77%
See 2 more Smart Citations
“…Although speculative, a more suitable evaluation of the mediation hypothesis would be provided by a measure of event-specific hopelessness which is more susceptible to influence by the negative life-event precipitating the depression and by other vulnerability factors. Research by Lynd-Stevenson (1995, 1996 with the unemployed provides preliminary support for the present formulation because when the BHS was reworded to include items applicable to the unemployed, the event-specific measure of hopelessness was found to mediate the full relationship between attributional style and depression. Lynd-Stevenson ( 1995, 1996 failed, however, to examine the mediation hypothesis for stress-depression relationships and did not evaluate the moderation hypothesis.…”
Section: Robed M Lynd-stevensonmentioning
confidence: 77%
“…Research by Lynd-Stevenson (1995, 1996 with the unemployed provides preliminary support for the present formulation because when the BHS was reworded to include items applicable to the unemployed, the event-specific measure of hopelessness was found to mediate the full relationship between attributional style and depression. Lynd-Stevenson ( 1995, 1996 failed, however, to examine the mediation hypothesis for stress-depression relationships and did not evaluate the moderation hypothesis. An empirical finding contrary to the present formation, nevertheless, is a study by DeVellis & Blalock ( 1992) who reported that a measure of event-specific hopelessness provided evidence supporting the moderation hypothesis but not the mediation hypothesis.…”
Section: Robed M Lynd-stevensonmentioning
confidence: 77%
See 1 more Smart Citation
“…These challenges have to 38 Julie Barlow et al be managed by the individual in all spheres of life, including employment. Given that unemployment itself is associated with increased vulnerability to depression and low self-esteem (MacKay Lynd-Stevenson, 1996;Sheeran et al, 1995;Vinokur et al, 1995), the combined impact of being unemployed and living with a disability warrants investigation. In this respect, pain and depression have been associated with instability of employment among people with rheumatoid arthritis (Fifield et al, 1992), with the fastest decline in employment occurring within the first 3 years of disease onset (Mau et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that a more optimistic attributional style, a construct closely related to cognitive vulnerability, has been related to less severe depressive symptoms among those who are unemployed (Lynd‐Stevenson, ; see also Winefield, Tiggemann, & Winefield, ; Bowman, ). In addition, negative attributional style predicted reduced likelihood of new employment in a sample of 62 unemployed men at a 3‐month follow‐up (Syzdek & Addis, ).…”
Section: Cognitive Behavioral Factorsmentioning
confidence: 99%